The Influence of Destination Image, Push and Pull Travel Motivation towards Tourist Loyalty through Tourist Satisfaction - Ermawati, Feni; Prihandono, Dorojatun (Universitas Negeri Semarang, 2018)
This study aims to examine the Tourist Loyalty in one tourism destination which is related to some variables such as Destination Image, Push Motivation, Pull Motivation And Tourist Satisfaction. The model used in this research is developed based on the existing literature. This research examines ten hypothesis of factors influencing the Tourist Loyalty in a tourism destination by the structures questionnaire which involve visitors of Dieng Plateau, Wonosobo regency. The result of the double regression analysis showed that (1) Destination Image, Push Motivation, and Pull Motivation directly influence Tourist Satisfaction; (2) Destination Image, Push Motivation, and Tourist Satisfaction directly influences the Tourist Loyalty (3) Pull Motivation does not influence directly toward Tourist Loyalty; (4) Destination Image, Push Motivation, and Pull Motivation influences the Tourist Loyalty by being mediated by Tourist Satisfaction. This research is expected to provide theoretical insights for next researchers and provide guidance for tourism management as an indicator in planing some efforts related to the development of the right tourism objects influencing the Tourist Loyalty.